2019
DOI: 10.1111/jne.12674
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal programming of stress responsiveness and behaviours: Progress and perspectives

Abstract: Parental exposure to stress or glucocorticoids either before or during pregnancy can have profound influences on neurodevelopment, neuroendocrine function and behaviours in offspring. Specific outcomes are dependent on the nature, intensity and timing of the exposure, as well as species, sex and age of the subject. Most recently, it has become evident that outcomes are not confined to first‐generation offspring and that there may be intergenerational and transgenerational transmission of effects. There has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 139 publications
(290 reference statements)
0
34
0
Order By: Relevance
“…Mechanistic studies in animals are linking early exposures to adversity with changes in gene regulatory mechanisms, including modifications of DNA methylation and altered levels of miRNA (Chan et al 2018, McGowan & Matthews 2018. Similar associations are emerging from recent human studies (Sasaki et al 2013, Hamada & Matthews 2019. Several genes associated with the regulation of HPA function and related behaviours are susceptible to altered epigenetic modulation.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Mechanistic studies in animals are linking early exposures to adversity with changes in gene regulatory mechanisms, including modifications of DNA methylation and altered levels of miRNA (Chan et al 2018, McGowan & Matthews 2018. Similar associations are emerging from recent human studies (Sasaki et al 2013, Hamada & Matthews 2019. Several genes associated with the regulation of HPA function and related behaviours are susceptible to altered epigenetic modulation.…”
Section: Introductionmentioning
confidence: 80%
“…Prenatal exposure to sGC has been shown to influence HPA and stress-related behaviours in offspring in a number of animal models, including primates, sheep, guinea pigs, rats and mice (Moisiadis & Matthews 2014, McGowan & Matthews 2018, Hamada & Matthews 2019. Studies from our group in the guinea pig have shown that single and repeated in utero exposure to sGC results in increased HPA responsiveness to a novel environment in juvenile offspring, with no effect on basal cortisol levels (Moisiadis et al 2017(Moisiadis et al , 2018.…”
Section: Synthetic Glucocorticoid Exposures During Pregnancymentioning
confidence: 97%
See 2 more Smart Citations
“…It has been shown that the gene expression and the DNA-methylation processes of babies are altered to adapt to the changing intrauterine environment. The methylation process of the genes such as Nr3c1, CRH, CRHBP, Crb,and Nr3c1 F1 promoter (see, e.g., Welberg & Seckl, 2001;Hamada & Matthews, 2019;McGowan & Matthews, 2017) would be altered. For instance, the Nr3c1 gene which controls the glucocorticoids receptor production and controls the HPA axis reactivity of babies.…”
Section: Stress and Cognitive Deficiencymentioning
confidence: 99%